Solar-Based Wireless Charging System for Electric Vehicles - Kumar S, Aravind; N, Yashaswini; S J, Rudresha; Kumar G R, Kiran (Journal of Power Electronics and Devices, 2023)
As the automobile industry enters a new era, it is transitioning quickly from IC engine vehicles to electric vehicles. The demand for electric vehicles is growing, which also increases the number of charging stations. In this paper, the automobile is charged wirelessly through inductive coupling using a wireless charging system. When electrical energy is transmitted over a distance from source to load without the use of conducting wires, it is referred to as wireless power transmission. A solar panel, battery, transformer, regulator circuits, copper coils, AC to DC converter, atmega controller and LCD are used in the system’s design. According to this technique, charging electric vehicles can be done while moving along and not at a charging station. Therefore, the technology supports the feasibility of a wireless, road-integrated, solar-powered EV charging system.